(untitled) (Bangladesh Journal of Medical Science, 2016)
Background: This is a Prospective observational study conducted in Department of Obstetrics and Gynaecology, BSMMU, Dhaka. Objective: The purpose of this study was to evaluate maternal and perinatal outcome of pregnancy with history of previous caesarean section. Method: Data were collected as per questionnaire by researchers herself by interviewing the patients and by observing the operations, investigation records and post-operative follow-up. A total number of 150 patients admitted with pregnancy with history of one or more previous caesarean section. Outcome measure: To find out antepartum complications, per-operative and post-operative complications specially related to previous caesarean section and to find out perinatal mortality and morbidity. Results: Among 150 patients who were delivered after one or more previous caesarean section, 88 (52%) patients had antepartum complications, the majority (88%) pregnancies were term pregnancy. The per-operative problem was difficulty to reach lower uterine segment due to adhesion with bladder was 16%. Overall post-operative complications were 20% cases. The common complications were wound infection (86%). Perinatal complications were 20 (30%) cases. Conclusion: The wide spread improvement in anaesthesia, surgical technique, antibiotics and blood transfusions have decreased the morbidity and mortality from caesarean section, but it is not without hazard. Bangladesh Journal of Medical Science Vol.15(3) 2016 p.392-398